2021
DOI: 10.1007/s10443-021-09919-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Dynamic Response and Failure Mechanisms for Composite Lattice Sandwich Structure under Different Slamming Loads

Abstract: This paper mainly investigates the slamming dynamic response and progressive damage evolution of the composite lattice sandwich structure under different slamming velocities and deadrise angles. Based on the Coupled Eulerian-Lagrangian (CEL) method, an integrated numerical model of sandwich structures is developed to simulate the slamming process, in which the progressive damage evolution of composite material is considered with VUMAT subroutine. The reliability and accuracy of the corresponding numerical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The dynamic response and the progressive damage evolution of composite lattice sandwich panels were investigated numerically using the coupled-Eulerian-Lagrangian method. [128][129][130] The study identified fibre fracture as the most significant damage mode and the need to optimize the structures in naval applications. Furthermore, the model accurately captured the phenomena of matrix cracking and delamination.…”
Section: Multi-scale Simulationsmentioning
confidence: 99%
“…The dynamic response and the progressive damage evolution of composite lattice sandwich panels were investigated numerically using the coupled-Eulerian-Lagrangian method. [128][129][130] The study identified fibre fracture as the most significant damage mode and the need to optimize the structures in naval applications. Furthermore, the model accurately captured the phenomena of matrix cracking and delamination.…”
Section: Multi-scale Simulationsmentioning
confidence: 99%
“…Sandwich panels (SP) are very promising components for structures since they ally high levels of specific stiffness and strength, as well as thermal and acoustic insulation. Due to their outstanding performance, these structures are used in applications where both high mechanical properties and low weight are desirable, such as aerospace, marine and automotive industries [1,2]. In these applications, the designed loading conditions must be accurately predictable, and so SP development is moving towards the design of specific configurations to ensure that minimized levels of cost and weight accompany maximized performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common applications of fiber-reinforced polymer composites is the manufacturing of the hulls of high-speed boats. The use of these new materials makes it possible to design lighter and stronger boats, which makes it easier to obtain complex geometries and allows one to adapt the mechanical properties of the material to the needs of the design [ 17 ]. Ocean structures and ships are subjected to repetitive impacts due to different causes (wave strikes, falling objects, collisions, and ice damage, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The energy dissipated in the material after impact is not distributed uniformly, but the orthotropy of the material allows the imposed stresses to respond differently in different directions. The stresses and strains of the laminate are not uniform and vary transversely between layers and depend on the type of composite material, the lamination sequence, and the orientation of the reinforcement fibers, making the type of damage produced different for each practical situation and, generally, difficult to predict without a previous experimental basis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%